2009
DOI: 10.3174/ajnr.a1464
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced MR Angiography Is Not More Accurate Than Unenhanced 2D Time-of-Flight MR Angiography for Determining ≥70% Internal Carotid Artery Stenosis

Abstract: BACKGROUND AND PURPOSE:Internal carotid artery (ICA) atheromatous disease is an important cause of ischemic stroke, and endarterectomy or stent placement is typically indicated for symptomatic patients with Ն70% stenosis. Our purpose was to compare contrast-enhanced MR angiography (CE-MRA) with unenhanced 2D time-of-flight MR angiography (2D TOF MRA) in detecting hemodynamically significant ICA stenosis, by using CT angiography (CTA) as the reference standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…30 Anzidei et al 31 reported that CTA was the most accurate technique for evaluating carotid stenosis in a large study group (n ϭ 170 patients), with a slightly better performance than MRA (97% versus 95% for steady-state MRA and 92% for first-pass MRA) and a greater accuracy than color Doppler ultrasonography (97% versus 76%). Although patients scheduled for carotid artery imaging are predominantly in the higher age group and radiation exposure is thought to be less critical, the ALARA (as low as reasonably achievable) concept should still be followed, and a variety of dose-reduction techniques in CT imaging have become available in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…30 Anzidei et al 31 reported that CTA was the most accurate technique for evaluating carotid stenosis in a large study group (n ϭ 170 patients), with a slightly better performance than MRA (97% versus 95% for steady-state MRA and 92% for first-pass MRA) and a greater accuracy than color Doppler ultrasonography (97% versus 76%). Although patients scheduled for carotid artery imaging are predominantly in the higher age group and radiation exposure is thought to be less critical, the ALARA (as low as reasonably achievable) concept should still be followed, and a variety of dose-reduction techniques in CT imaging have become available in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis was categorized as 70%-95% or Ͼ 95%-99% by use of a method adapted from a study of diagnostic accuracy of TOF MRA in high-grade carotid artery stenosis. 16 We used MRA MIP images to visually estimate the degree of stenosis, taking into account maximal luminal diameter stenosis relative to the caliber of normal-appearing distal ICA on MIP images, and used axial 3D-TOF source images to confirm stenosis measurements when MIP data did not provide unequivocal assessment of stenosis. Because measurements by use of the distal ICA as the denominator for stenosis measurements might underestimate the degree of stenosis in near-occlusion, as per North American Symptomatic Carotid Endarterectomy Trial guidelines, 17 NASCET-type measurements were not used in such cases.…”
Section: Imaging Data Assessmentmentioning
confidence: 99%
“…Although DSA was the standard method for evaluating carotid stenosis to date, TOF-MRA was a frequently used imaging technique in a clinical setting because of its non-invasiveness and absence of need for contrast injection. Although TOF-MRA was known to be sensitive to artifacts, there was also increasing evidence that TOF-MRA has similar accuracy or it could even be more accurate than CE-MRA, especially in severe grade stenosis (23)(24)(25). Third, we evaluated the percentage of luminal stenosis as an indicator of plaque progression.…”
Section: Discussionmentioning
confidence: 99%